Meningkatkan Prestasi Belajar Siswa Mata Pelajaran PKn dengan Metode Role Playing di SDN IV Gunung Rajak - Ahmad Izzuddin (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2017)
This classroom action research aims to improve student achievement by applying role playing method in civic education education material impact of globalization. There are several problems found in the field observation, among others, the low achievement of students in civic education learning (Civics) with several factors that influence, among others, from students, families, material understanding, teachers and the use of teaching aids. Furthermore, by using the role playing method, the writer found a good learning achievement change that is from the result of data analysis of student's learning skill in class, reaching the average value of cycle class I is 67,50 and on second cycle equal to 77,50 and increase as big as 10.00, with completeness level in cycle I equal to 65,55%. In the second cycle of 95.45% Achievement of power seraf in cycle I 73.82%, the second cycle of 79.52% so that an increase of 5.70%